Thyroid scintigraphy in the era of fine‐needle aspiration cytology. (17th December 2020) - Pirola, Ilenia; Di Lodovico, Elena; Casella, Claudio; Pezzaioli, Letizia; Facondo, Paolo; Ferlin, Alberto; Lombardi, Davide; Cappelli, Carlo
Abstract: Purpose: To evaluate whether thyroid scintigraphy would alter the clinical management of patients referred for fine‐needle aspiration cytology (FNA). Methods: We reviewed the medical and imaging records of patients referred to our Department between 2016 and 2019. All the patients had to take a serum thyrotropin test administered in our hospital at least two months before the FNA; where the TSH level was ≤1.5 mIU/L, the patients were subjected to a scan and subsequently to FNA, where indicated. We selected only healthy patients with no previous history of thyroid disease, who were not taking any drugs and who had a TSH level of ≤1.5 mIU/L. We excluded patients with multinodular goitre. Results: A total of 176 patients were analysed. A total of 67/176 patients (38%) showed a serum of TSH ≤ 0.27 mIU/L. Scintigraphy identified a hot nodule in 142 lesions (80.7%), a warm nodule in 8 lesions (4.5%) and a cold nodule in 26 lesions (14.8%). The ROC curve analysis indicated that a TSH value of ≤0.42 mIU/L identified patients with hyperfunctioning nodules with a sensitivity of 65% and a specificity of 77%. All patients with cold and warm nodules were submitted to FNA: 22/26 (85%) and 5/8 (63%) lesions showed suspected malignancy or were compatible with malignancy, respectively. Conclusion: Speculating on our data, if we had subjected our patients to FNA as indicated by the 2015 ATA guidelines, we would have subjected 117 patients to cytology, from whom 83 had undetected hot nodules. Conversely, by adopting scintigraphy for all patients with TSH ≤ 1.5 mIU/L, 109 patients have avoided FNA. However, our study was performed in a region with a history of mild iodine deficiency. Therefore, we cannot claim that our observation is valid for patients born and living in areas with sufficient iodine uptake. We recommend thyroid scintigraphy for treating single thyroid nodules in euthyroid patients born and living in regions with an iodine deficiency, when TSH levels are below 1.5 mIU/L before FNA.